Protocol for precision editing of endogenous Chlamydomonas reinhardtii genes with CRISPR-Cas - Adrian Pascal Nievergelt; Dennis Ray Diener; Aliona Bogdanova; Thomas Brown; Gaia Pigino (STAR Protocols, 2024)
Summary: CRISPR-Cas genome engineering in the unicellular green algal model Chlamydomonas reinhardtii has until recently suffered from low integration efficiencies despite traditional genetics being well established. Here, we present a protocol for efficient homology-directed knockin mutagenesis in all commonly used strains of Chlamydomonas. We describe steps for scarless integration of fusion tags and sequence modifications of almost all proteins without the need for a preceding mutant line. We further empower this genetic-editing approach by efficient crossing and highly robust screening protocols.For complete details on the use and execution of this protocol, please refer to Nievergelt et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.